Coronary Artery Disease Is Associated with an Increased Amount of T Lymphocytes in Human Epicardial Adipose Tissue - Miloš Mráz; Anna Cinkajzlová; Jana Kloučková; Zdeňka Lacinová; Helena Kratochvílová; Michal Lipš; Michal Pořízka; Petr Kopecký; Aneta Pierzynová; Tomáš Kučera; Vojtěch Melenovský; Ilja Stříž; et al. (Hindawi Limited, 2019)
Immunocompetent cells including lymphocytes play a key role in the development of adipose tissue inflammation and obesity-related cardiovascular complications. The aim of the study was to explore the relationship between epicardial adipose tissue lymphocytes and coronary artery disease (CAD). To this end, we studied the content and phenotype of lymphocytes in peripheral blood, subcutaneous adipose tissue (SAT), and epicardial adipose tissue (EAT) in subjects with and without CAD undergoing elective cardiac surgery. Eleven subjects without CAD (non-CAD group) and 22 age-, BMI-, and HbA1C-matched individuals with CAD were included into the study. Blood, SAT, and EAT samples were obtained at the beginning of surgery. Lymphocyte populations were quantified as % of CD45+ cells using flow cytometry. Subjects with CAD had a higher total lymphocyte amount in EAT compared with SAT (32.24±7.45 vs. 11.22±1.34%, p=0.025) with a similar trend observed in non-CAD subjects (29.68±7.61 vs. 10.13±2.01%, p=0.067). T (CD3+) cells were increased (75.33±2.18 vs. 65.24±4.49%, p=0.032) and CD3- cells decreased (21.17±2.26 vs. 31.64±4.40%, p=0.028) in EAT of CAD relative to the non-CAD group. In both groups, EAT showed an elevated percentage of B cells (5.22±2.43 vs. 0.96±0.21%, p=0.039 for CAD and 12.49±5.83 vs. 1.16±0.19%, p=0.016 for non-CAD) and reduced natural killer (NK) cells (5.96±1.32 vs. 13.22±2.10%, p=0.012 for CAD and 5.32±1.97 vs. 13.81±2.72%, p=0.022 for non-CAD) relative to SAT. In conclusion, epicardial adipose tissue in subjects with CAD shows an increased amount of T lymphocytes relative to non-CAD individuals as well as a higher number of total and B lymphocytes and reduced NK cells as compared with corresponding SAT. These changes could contribute to the development of local inflammation and coronary atherosclerosis.